(untitled) (Journal of Patan Academy of Health Sciences, 2018)
Introductions: A ‘health humanity’ (HH) module was facilitated for second semester medicine and first semester nursing students at the American International Medical University, Saint Lucia from September to November 2017. The study was conducted during the third week of November to obtain participant perceptions about the module and suggestions for further improvement. Methods: Students were explained the aims and objectives of the study and invited to participate. Certain demographic information was noted. Participants indicated their degree of agreement with a set of 16 statements using a five-point scale. They were asked with which particular session, role-play and painting they identified with the most. Two suggestions to further improve the use of role-plays, future modules, interprofessional learning and paintings were also elicited. Results: Twenty-six of the 28 students (92.8%) participated with most being either Indian or Saint Lucians from urban backgrounds. The median agreement score with various statements was 4 or above. Participants identified most with the session on ‘death and dying’, ‘empathy’ and ‘health science student’; with the painting ‘tree of hope’; and the scenario ‘where a female medical student falls in love with a boy who was not reciprocating her feelings and with a girl who is trafficked, forced to become a sex worker returning to her family with HIV-positive. Participants agreed that the module promoted interprofessional learning. Conclusions: Student feedback about the module was positive. It provided a platform to promote interprofessional learning among the participants, medical and nursing students.